2017
DOI: 10.1002/etep.2327
|View full text |Cite
|
Sign up to set email alerts
|

Predictive out-of-step relay based on equal area criterion and PMU data

Abstract: This paper proposes a novel-predictive and setting-free out-of-step protection technique based on synchronized phasor measurements and equal area criterion. Generator instability is predicted by comparing the acceleration and deceleration areas corresponding to the fault and postfault conditions, respectively. For each generator, the acceleration area during fault condition is calculated directly using the generator output power and rotor angle in real time. As soon as the fault is cleared, the deceleration ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…In Reference 86, a new method for the OOS prediction of the alternator is proposed, by transforming the system into its Thevenin's Equivalent (TE). For obtaining the online TE of system, the algorithm utilizes the PMU data.…”
Section: Methods Used In Sips Implementationmentioning
confidence: 99%
“…In Reference 86, a new method for the OOS prediction of the alternator is proposed, by transforming the system into its Thevenin's Equivalent (TE). For obtaining the online TE of system, the algorithm utilizes the PMU data.…”
Section: Methods Used In Sips Implementationmentioning
confidence: 99%
“…For instance, LOE can be detected, using impedance (Z) [14,15], active power [16], or a combined index of other parameters such as load angle (δ), stator voltage or current, air-gap flux and reactive power [17][18][19][20][21]. Furthermore, OOS is another significant protection which can be detected by P and δ based on equal area criteria [22][23][24][25][26]. Therefore, the successful experience of using generator parameters in detection of LOE and OOS becomes the best motivation for the authors to find out a novel parameter-based method for generators RP protection to improve the speed and security of the previous unsuitable methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Sobbouhi and Aghamohammadi, a prediction algorithm based on the locus of rotor speed‐acceleration variation constructed from data obtained by PMU measurements is proposed and applied to a large‐scale realistic power system. In Alinezhad et al, by calculating postfault Thévenin equivalent from synchronized phasor measurements and based on equal area criterion, an OOS predictive technique is presented from which by calculating the acceleration and deceleration areas corresponding to the fault and postfault conditions, an OOS condition is predicted. In Zhang and Zhang, by using voltage phase angles of buses measured by using PMU, a new concept of coordinate transformation is presented from which the OOS centre is positioned and the splitting strategy is determined.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that generally the algorithms for recognizing OOS condition can be categorized into 2 groups: detection algorithms [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and prediction algorithms. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In Table 1, it is concluded that a number of conventional methods including an adaptive OOS relay, based on the classical equal area criterion using power angle (P-δ), are proposed in which the newly developed technology of synchronized phasor measurements plays an important role. 2 In Taylor et al, 3 the property of the rate of change of apparent impedance is used for proposing an OOS relaying scheme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation